EFEKTIVITAS ABDOMINAL STRETCHING EXERCISE DALAM MENURUNKAN DISMENORE PADA MAHASISWI KEPERAWATAN - ainil fitri; Yasinta Yasinta (Jurnal Keperawatan Abdurrab, 2024)
A complaint that often appears during menstruation is menstrual pain (dysmenorrhea). Abdominal stretching exercise is an exercise technique to stretch the abdominal muscles. The purpose of this study is to determine the effectiveness of abdominal stretching exercise in reducing menstrual pain (dysmenorrhea) in female nursing students of Abdurrab University. This study is a quantitative research with a pre-experimental research design (one group pretest and posttest). The population in this study is all nursing students totaling 102 female students. The sampling technique is the Random Sampling technique with a resonant number of 30 respondents. The research instrument used Numerical Rating Scale (NRS) before and after the administration of abdominal stretching exercise, and used an abdominal stretching exercise logbook. Based on the results of the research carried out, after being given the abdominal stretching exercise technique on the second day, 83.3% of respondents experienced a decrease in menstrual pain (dysmenorrhea), only 16.7% of respondents had not experienced a decrease in the intensity of menstrual pain (dysmenorrhea). This means that there is an effect of giving abdominal stretching exercise techniques to female students who experience dysmenorrhea during the menstrual process. It is expected that respondents will apply abdominal stretching exercises when experiencing dysmenorrhea, as well as provide information and teach about abdominal stretching exercises to known people who are also experiencing the same problem.